The faces of Africa : diversity and progress; repression and struggle - United States. Congress. House. Committee on Foreign Affairs (Washington, D.C. US Government Printing, 1972)
This book contains reports that were submitted to the Committee on Foreign Affairs by the Special Study Mission Africa conducted between February 7- March 7, 1971
asm 22/01/2019
Loans
Keywords: Diplomatic relations; Politics and government; United States; Africa